Classic prognostic factors in patients with soft tissue sarcomas - Dymek, Paweł; Walasek, Tomasz; Mucha-Małecka, Anna; Kukiełka, Andrzej; Dąbkowski, Mateusz (Contemporary Oncology/Współczesna Onkologia, 2007)
Soft tissue sarcomas (STS) comprise a heterogeneous group of tumours, presenting various clinicopathologic features. Prognostic factors for overall survival, disease-free survival, local recurrence and metastatic recurrence are different. The role of the following independent adverse prognostic factors are presented and discussed: age and sex of patients with STS, duration of tumour-related symptoms, the histological subtypes and grade of differentiation of tumour, its size and location, quality of surgical margins and AJCC/UICC staging.